"Zum usbekischen Nasreddin-repertoire." - Stein, Heidi.
Permanent International Altaistic Conference (33: 1990: Budapest). Budapest, Research Group for Altaic Studies, Hungarian Academy of Sciences, 1992. 331-335 ss.